AUSPEX: a graphical tool for X‐ray diffraction data analysis. Issue 9 (6th September 2017) - Thorn, Andrea; Parkhurst, James; Emsley, Paul; Nicholls, Robert A.; Vollmar, Melanie; Evans, Gwyndaf; Murshudov, Garib N.
Abstract : AUSPEX is a new software tool for the statistical analysis of single‐crystal X‐ray diffraction data. It can be used to identify problems in the data resulting from the experiment itself, image processing, data scaling or conversion. Abstract : In this paper, AUSPEX, a new software tool for experimental X‐ray data analysis, is presented. Exploring the behaviour of diffraction intensities and the associated estimated uncertainties facilitates the discovery of underlying problems and can help users to improve their data acquisition and processing in order to obtain better structural models. The program enables users to inspect the distribution of observed intensities (or amplitudes) against resolution as well as the associated estimated uncertainties (sigmas). It is demonstrated how AUSPEX can be used to visually and automatically detect ice‐ring artefacts in integrated X‐ray diffraction data. Such artefacts can hamper structure determination, but may be difficult to identify from the raw diffraction images produced by modern pixel detectors. The analysis suggests that a significant portion of the data sets deposited in the PDB contain ice‐ring artefacts. Furthermore, it is demonstrated how other problems in experimental X‐ray data caused, for example, by scaling and data‐conversion procedures can be detected by AUSPEX .